On properties of solutions of a limit problem for systems of nonlinear functional differential equations of neutral type - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
For a class of systems of nonlinear differential-functional equations, we study asymptotic characteristics of their solutions continuously differentiable and bounded for t > T > 0 (along with the first derivative).